Growth, development and quality of wax apple (Syzygium samarangense [Blume] Merrill & L. M. Perry) fruits as influenced by selected horticultural techniques / Mohammad Moneruzzaman Khandaker - Khandaker, Mohammad Moneruzzaman (2012)
Plant growth regulators, regulating chemicals and growth manipulating techniques are important tools in horticulture. These techniques can regulate various physiological and biochemical aspects of growth and development, and improve growth, yield and nutritional quality of fruits. Currently, there is a limited report if any, describing how plant growth regulators (PGRs) affect the fruit quality of wax apple, an increasingly popular fruit in Asia. The present study was carried out to investigate the effects of plant growth regulators, gibberellic acid (GA3) at 20, 50 and 100 mg/L, 2, 4-dichlorophenoxy acetic acid (2,4-D) and naphthalene acetic acid (NAA) at 5, 10 and 20 mg/L, girdling practices (50%, 100%, I, C and V-shaped) and hydrogen peroxide (H2O2) at 5, 20 and 50 mM on the growth, development and quality of the wax apple (Syzygium samarangense) var. Jambu Air Madu fruits Various physiological, biochemical and phytochemical parameters were monitored during three seasons of fruit growth between December, 2008 to May, 2011 at MARDI, Jalan Kebun, Klang, and a farm in Banting. The results showed that the application of GA3 enhanced fruit growth, increased fruit length, diameter and color development, fruit number, weight and yield. GA3 also increased the number of buds and fruit set and reduced bud and fruit drop. With regard to fruit quality, the application of GA3 increased fruit juice, biomass, total soluble solids (TSS), glucose, fructose, sucrose, total sugar, sugar acid ratio, soluble protein and total flavonoids content in the fruits. In addition, anthocyanin content, total phenol, ascorbic acid and antioxidant activity was higher in GA3-treated fruits. Less titrable acidity was also recorded in treated fruits. Treatment with 2, 4-D enhanced bud development, fruit growth, fruit length and diameter, peel color development and increased fruit set, yields, and fruit drymatter. The treatment also reduced bud and fruit drop. Chlorophyll fluorescence, photosynthetic yield, stomatal conductance and chlorophyll readings were also high in 2, 4-D-treated branches. Fruit quality parameters such as TSS, total sugar and anthocyanin content were also high in the treated fruits. NAA treatments increased bud number and total number of fruits, enhanced faster fruit growth, fruit size and red color development. Furthermore, NAA treatment increased photosynthetic quantum yield, chlorophyll content, stomatal conductivity, fruit set, fruit weight and total yield in addition to decreasing fruit drop. With regard to fruit quality, NAA treatment increased TSS, fruit juice, total sugar, phenol, flavonoid contents and higher antioxidant activity in the fruits, in addition to a higher anthocyanin, protein content and phenylalanine ammonia lyase (PAL) activity. Girdling significantly increased fruit growth and development, and color development. Apart from improving leaf physiological characteristics, girdling also increased juice K+ content, TSS, total sugars, total phenolics, flavonoids and anthocyanin content. A higher antioxidant activity in the fruit was also observed. Leaf chlorophyll content and dry matter, total soluble solids and total sugar contents of fruits were significantly increased in wax apple after treatment with H2O2. The application of H2O2 significantly reduced bud drop and enhanced fruit growth, resulting in larger fruit size, increased fruit set, fruit number, fruit biomass and yield. H2O2 treatment increased the K+, anthocyanin, carotenoid, flavonoid, phenolic and soluble protein content. Higher PAL and antioxidant activities were measured in the treated fruits. There was a positive correlation between peel color and TSS and anthocyanin, stomatal conductance with photosynthesis and yield, phenols and flavonoids with antioxidant activity, PAL activity and anthocyanin formation. Finally, net photosynthesis, stomatal conductance and transpiration, leaf chlorophyll and dry matter content in the leaves of the wax apple were significantly increased after GA3 and H2O2 treatments. Sucrose phosphate synthase (SPS) activity and rubisco expression was also high in GA3 treatments. In addition, a higher soluble protein content, PAL and anthocyanin formation were recorded in the treated fruits. From this study, it can be concluded that spraying PGRs ( 50 mg/L GA3, 10 mg/L NAA or 2, 4-D), 20 mM H2O2 and C-shaped girdling application results in better yield and quality of wax apple fruits under field conditions.